Chloroplast gene sequences and the study of plant evolution. - Clegg, M T (1993)
A large body of sequence data has accumulated for the chloroplast-encoded gene ribulose-1,5-biphosphate carboxylase/oxygenase (rbcL) as the result of a cooperative effort involving many laboratories. The data span all seed plants, including most major lineages from the angiosperms, and as such they provide an unprecedented opportunity to study plant evolutionary history. The full analysis of this large data set poses many problems and opportunities for plant evolutionary biologists and for biostatisticians.